Estudio de pre-factibilidad para la implementación de una planta de producción de crema hidratante a base de camu camu y jalea real - Rojas Torres, Lilian (2015)
The main objective of the following research is to determine the successful of installing a factory of a hydrating body lotion of Camu camu and Royal jelly. Nowadays, the hygiene and personal care market is one of the most rentable business because the more someone invest in this topic the better personal image in a healthy body they will have.